Pelatihan Desain dan Sosial Media Marketing Produk Agricultural SMK Negeri 1 Petang - Darma Yasa, Ngakan Putu; Jayanegara, I Nyoman; Fajaraditya Setiawan, I Nyoman Anom; Putra Yasa, I Wayan Adi; Trisemarawima, I Nyoman Yoga (Universitas Pahlawan Tuanku Tambusai, 2025)
Becoming a young entrepreneur is also implemented by one of the State Vocational Schools in Petang District, Badung Regency, Bali. State Vocational High School 1 Petang has one major in Agricultural Product Processing, namely producing products that are ready to be sold, such as cakes and various types of drinks. The student's production has been sold only within the school environment. Lack of knowledge of technology, namely marketing products via the internet, is an obstacle. This is caused by a lack of resources who understand the use of technology such as creating designs, packaging products and marketing them. To overcome this problem, design and social media marketing training was carried out to market the product. The method applied in this training is direct mentoring for five days in the classrooms of SMK Negeri 1 Petang. The material provided is making promotional designs and video reels that are uploaded on social media. The results of this training show that the students were very enthusiastic in taking part in the training and succeeded in designing content for promotion purposes on social media.